PRESENCE OF Streptococcus Mutans IN SALIVA AND ITS RELATIONSHIP WITH DENTAL CARIES: ANTIMICROBIAL SUSCEPTIBILITY OF THE ISOLATES - Gamboa, Fredy; Departamento de Microbiología, Facultad de Ciencias. Pontificia Universidad Javeriana, Bogotá. Centro de Investigaciones Odontológicas, Facultad de Odontología. Pontificia Universidad Javeriana, Bogotá (2004)
Dental caries is a localized, transmissible, pathological infectious process that ends up in the destruction of hard dental tissue. Streptococcus mutans is considered to be the main cause of dental caries. Indeed, numerous reports have shown the close relationship between salivary levels of S. mutans and dental caries. The purpose of this study was to determine the relationship between the presence of Streptococcus mutans and dental caries, and to evaluate the antimicrobial susceptibility of the isolates. Unstimulated saliva was collected from 53 3 to 5-year-old children from the Diego Torres school in Turmequé (Boyacá,Colombia). Saliva samples were vortexed and serially diluted in 0.05 M phosphate buffer. Aliquots of 100ul of the appropriate dilutions were cultured on Mitis Salivarius Bacitracin agar medium for the selective isolation of S. mutans, and incubated anaerobically for two days at 37o C. The minimal inhibitory concentrations of the S. mutans isolates were evaluated against penicillin, amoxicillin, cefazolin, erythromycin, clindamycin, imipenem and vancomycin by an agar dilution method. The dental caries experience in these children was 66% (35/53) and S. mutans was found in the saliva of 33 children (62%);21 of them had dental caries and 12 did not. In the 20 children from whom S. mutans was not isolated, 14(70%) were found to have caries. There were no statistically significant differences in S. mutans counts between the group with dental caries and the caries-free group (p=0.21). All isolates were highly sensitive to penicillin, amoxycillin, cefazolin, erythromycin, clindamycin, imipenem and vancomycin; 50 and90% of the strains from S. mutans were inhibited by concentrations of less than 0.12 and 0.5 ug/ml, respectively, for all antibiotics studied. In conclusion, not all of the children hosting this microorganism had caries, and the S. mutans strains were highly sensitive to the antibiotics tested.